2012 IEEE Sixth International Conference on Software Security and Reliability 2012
DOI: 10.1109/sere.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Simplification of Obfuscated JavaScript Code: A Semantics-Based Approach

Abstract: Abstract. Javascript is a scripting language that is commonly used to create sophisticated interactive client-side web applications. It can also be used to carry out browser-based attacks on users. Malicious JavaScript code is usually highly obfuscated, making detection a challenge. This paper describes a simple approach to deobfuscation of JavaScript code based on dynamic analysis and slicing. Experiments using a prototype implementation indicate that our approach is able to penetrate multiple layers of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…In order to face this problem, researchers have recently started to consider semantic approaches to malware detection in order to deal with metamorphism, i.e., obfuscation, (e.g., see [9,11,16,29,[26][27][28]32]). …”
Section: Related Workmentioning
confidence: 99%
“…In order to face this problem, researchers have recently started to consider semantic approaches to malware detection in order to deal with metamorphism, i.e., obfuscation, (e.g., see [9,11,16,29,[26][27][28]32]). …”
Section: Related Workmentioning
confidence: 99%
“…In the following subsections, we briefly discuss the major obfuscation techniques being used in wild [7].…”
Section: A Javascript Obfuscation Techniquesmentioning
confidence: 99%
“…They also found that 71% of malicious JavaScript files are obfuscated while 30% of them use at least two types of obfuscation. By collecting bytecode execution paths from the analysed file, applying dynamic slicing and code transformations, the authors in [14] have managed to create a system that is able to deobfuscate several layers of the target program.…”
Section: Related Workmentioning
confidence: 99%